Helping the Helpers: A Photovoice Study Examining Burnout and Self-Care among HIV Providers and Managers. Issue 3 (26th May 2020) - Rahman, Rahbel; Ghesquiere, Angela; Spector, Anya Y.; Goldberg, Rebecca; Gonzalez, Olga M.
ABSTRACT: Photovoice was used among 4 HIV providers and 4 managers at a NYC community-based HIV organization to engage in critical dialogs about the way they experience burnout and self-care measures taken. The study's objective was to empower participants to change aspects of their organizational culture and advocate for better working conditions to mitigate burnout. Common themes around causes of burnout were: perfectionism, isolation, multitasking, conflict in relationships. Common themes around self-care practices were: physical activity, recreational activities, being in nature, spirituality, self-expression, food/drinks, social support. The study offers strategies to social service agencies to inspire providers to create organizational change.